The Imperativeness of Curriculum Improvement of Diniyah Education at the Wustha Level in South Kalimantan - Hamdan, Hamdan (IAIN Samarinda, 2020)
Islamic educational institutions in South Kalimantan are mushrooming both formally and informally. It is because Muslims are predominantly. They are known to be very religious and even steadfast in applying Islamic values. Most of the educational institutions grow and develop at the initiative of community members (self-help). The distribution of Islamic Religious and Religious Education Institutions in South Kalimantan is 582 institutions. This shows the potential as well as the great responsibility that is carried out in helping the government to realize the goals of National Education. However, it is unfortunate that the diniyah education curriculum experiences stagnation does not up to date. It is not connected to the needs and expectations of the community. It is due to the curriculum tends to focus more on the teacher center. Therefore, the curriculum needs to be adjusted to the needs and expectations of the community. Hence, there is no gap between educational institutions and the community. The research method of this study used Research and Development (R&D). The approach used 2 steps, namely preliminary activities and curriculum improvement (development). The data resources obtained from questionnaires, interviews, observations, and documentaries. Participants are ustadz/ustadzah who teach subjects on diniyah curriculum, experts, and graduates. The results of this study indicate that the curriculum for diniyah education especially the wustha level in South Kalimantan is needed to be revised or developed. The curriculum should be adjusted to the aspirations, needs, and expectations of the community.